Detailed description of some mantis shrimp larvae and their implication for the character evolution within Stomatopoda - Wiethase,Joris (2020)
Abstract We present a documentation of the morphological details of two larval stages of mantis shrimps. Documentation was done using the autofluorescence capacities of the cuticle. This is the first time that morphological details of late mantis shrimp larvae are documented in great detail via photography, including all parts of the body up to the proximal elements of the appendages, and not presented as line drawings; it is the second time for mantis shrimp larvae in general. The description is presented as a standardized descriptive matrix. Documentation and description style are adjusted to facilitate comparison with fossil representatives of mantis shrimps, but also their extant counterparts, as well as specimens in the wider framework of Malacostraca and Eucrustacea. Through an exemplary comparison with fossil mantis shrimps, we provide indications about the early evolutionary history of the group. Through an out-group comparison, we identify several possible evolutionary changes of developmental timing, i.e., heterochrony, which could explain some morphological specialisations of mantis shrimps.